Heavy metals in Bangkal (Nauclea sp.) leaves and stems from Mangonbangon River, Tacloban City implications on phytoremediation - Navarra, Jim S.
One of the most concerning issues that our world currently faces is heavy metal pollution. Although several studies suggested solutions to the ongoing problem, these solutions still result to further complications. Instead, a green technology is recommended to address the issue and that is through phytoremediation. This study was then conducted to examine the heavy metal content in the leaves and stems of bangkal (Nauclea sp.) tree along Mangonbangon river, a heavy metal polluted river in Tacloban City, to assess its implication to phytoremediation. Leaf and stem samples were collected from different bangkal trees and subsequently processed and analyzed through an Atomic Emission Spectrophotometer (MP-AES). The results from the analyses showed the presence of the following heavy metals in the plant tissues: Pb, Cu, Ni, Mn, and Fe. Among these, only Pb was considered extremely toxic to human health. The statistical analysis revealed that there was no significant difference in the Pb concentration in the leaves and stems of Bangkal from different stations in Mangonbangon River. Also, there was no significant difference in the Pb concentration in the leaves and stems of bangkal between the experimental and control group. The results suggest that bangkal is a potential bioaccumulator of heavy metal and capable of absorbing heavy metals at similar rates regardless of its location or conditions. However, to further support the ability of the plant to uptake heavy metals in different substrates and environmental conditions, it is recommended to also conduct an analysis on the heavy metals in the soil and water from where the samples were collected.